Radiocarbon Dating of Bones at the LARA Laboratory in Bern, Switzerland. Issue 3 (15th November 2016) - Szidat, Sönke; Vogel, Edith; Gubler, Regula; Lösch, Sandra
Abstract: The Laboratory for the Analysis of Radiocarbon with AMS (LARA) was established at the University of Bern in 2013. Since then, the quality of sample preparation and radiocarbon measurement procedures have been validated for different materials such as plant remains, macrofossils, bulk sediment, charcoals, and wood. This article presents the optimization of sample pretreatment of bones based on protocols described in the literature. The extraction of collagen was performed with an acid-base-acid treatment, gelatinization, coarse filtration, lyophilization, and graphitization. Dating results were validated as satisfactory for the Holocene by investigation of 36 individual samples previously dated by other 14 C laboratories including VIRI/SIRI materials and from well-known archaeological contexts. An additional blank contribution for bone treatment was determined by comparison with the preparation of other sample materials. The cases of two outliers from the Holocene were studied in detail.